Enhancing Students’ Higher-Order Thinking Skills Through Inquiry-Based e-LKPD on Boyle’s Law - Daman Saputri, Nadiyah; Distrik, I Wayan; Herlina, Kartini (Department of Physics Education, Universitas Mataram, 2025)
This study aimed to examine the effect of higher-order thinking skills (HOTS) through the implementation of an inquiry-based electronic student worksheet (e-LKPD) on Boyle’s Law material. The participants were students from class XI IPA 1, who served as the experimental group, and class XI IPA 2, who served as the control group at SMA Negeri 1 Pekalongan. A quasi-experimental method with a pretest-posttest group design was employed. The study involved two variables: the independent variable (the inquiry-based e-LKPD on Boyle’s Law) and the dependent variable (students’ higher-order thinking skills). Data were analyzed using N-gain analysis, an Independent Samples t-test, and an effect size calculation. The N-gain results showed an improvement in HOTS in the experimental group with a score of 0.65 (moderate category), while the control group scored 0.49 (also in the moderate category). The Independent Samples t-test produced a sig. (2-tailed) value of 0.000, indicating a significant difference in HOTS between the experimental and control groups. Additionally, the effect size analysis yielded a Cohen’s d value of 1.715, classified as a large effect. These results indicate that the use of an inquiry-based e-LKPD had a substantial impact on enhancing students’ higher-order thinking skills. In conclusion, implementing inquiry-based e-LKPD in teaching Boyle’s Law significantly improves students' ability to think at higher cognitive levels.